PENGUNGKAPAN INTELLECTUAL CAPITAL DAN NILAI PASAR EKUITAS TERHADAP BIAYA MODAL EKUITAS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2020-2023) - Siti Rohmah; Martinus Robert Hutauruk; Hariyanti Sitohang (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze the effect of Intellectual Capital disclosure and market equity value on the cost of equity capital in LQ-45 companies listed on the Indonesia Stock Exchange for the period 2020–2023. The background of this research is based on the importance of capital cost efficiency in supporting financing strategies and enhancing firm value amid dynamic capital market competition. This quantitative study uses secondary data obtained from annual financial reports, with samples selected through purposive sampling. The analysis method employed is multiple linear regression to examine both partial and simultaneous effects of the independent variables on the dependent variable. The results show that both Intellectual Capital disclosure and market equity value have a significant influence on the cost of equity capital. These findings imply that companies need to manage and communicate intellectual asset information effectively while also strengthening their market position to reduce capital costs. This research is expected to serve as a reference for companies and investors in understanding the importance of transparency and market value in achieving funding efficiency.